Comparison and Computational Performance of Tsunami-HySEA and MOST Models for LANTEX 2013 Scenario: Impact Assessment on Puerto Rico Coasts. - Macías-Sánchez, Jorge; Mercado, Aurelio; González-Vida, José Manuel; Ortega-Acosta, Sergio; Castro-Díaz, Manuel Jesús (Springer Nature, 2016)
HySEA tsunami model is used to simulate the Caribbean LANTEX 2013 scenario. The numerical simulation of the propagation and inundation phases is performed with a single integrated model but using different mesh resolutions and nested meshes. Special emphasis is put on assessing the most exposed coastal areas at Puerto Rico affected by this event. Comparisons with MOST are made considering both time series at different locations, and inundation maps. Both models compare well for propagating tsunami waves in open sea, producing very similar results. The main discrepancies are observed in coastal areas, where maximum wave height provided by the propagation module of MOST is different from the one provided by HySEA. The main reason is that, while HySEA always compute inundation effects, MOST propagation does not include runup physics and locates an artificial numerical reflecting wall at a certain depth (typically 20 m). Henceforth, in nearshore shallow waters HySEA should be compared with the inundation version of MOST. Nevertheless the most striking difference resides in computational time; HySEA is coded using the advantages of GPU architecture, and can produce a 4 hour simulation in a 60 arc-sec resolution for the whole Caribbean Sea in less than 4 min with a single GPU and as fast as 11 seconds with 32 GPUs. When details about the inundation must be simulated, a 1 arc-sec (approximately 30 m) inundation resolution mesh covering all of Puerto Rico, an island with dimensions of 160 km east-west and 56 km north-south, is used, and a three level nested meshes technique implemented. In this case approximately 11 hours of wall clock time are needed for a 2 hour simulation in a single GPU.
https://openpolicyfinder.jisc.ac.uk/id/publication/11803
Keywords: Maremotos; Tsunami-HySEA model; MOST model; Tsunamis; Numerical simulation